PELATIHAN BUDIDAYA JAMUR TIRAM DI DESA BELANGA KINTAMANI - SUKEWIJAYA, SUKEWIJAYA; DWIYANI, I M., RINDANG; MAYUN, I.A.; MAYADEWI, N.N. ARI; SEMARAJAYA, COK. G.A. (Buletin Udayana Mengabdi, 2012)
ABSTRACT Nowadays, demand of mushroom increase along with the changing of consume pattern which concerning on various and the quality of food, however, their supply relatively low. Low knowledge and skill of mushroom producer is one of limitation. Belanga rural community potentially develop cause of their natural resources, hence the knowledge and skill need to be improved by workshop. The workshop was covered the member farmer’s organization of Belanga (Subak Abian) by planting method and postharvest including their marketing. Field trip to mushroom producer and by monitoring and evaluating of workshop topic included to this workshop. At the present, the farmer was produced the oyster mushroom even if on small scale area. Confidently, by their improved skill of oyster mushroom farmers financial in Belanga may perhaps be enhanced.